(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this study is to analyze financial inclusion in Congo from a household survey. Financial inclusion in Congo remains at a low level as there is a small proportion of people with accounts in banks and microfinance. In addition, these people are using less and less financial services. Econometric analysis has shown that financial inclusion is determined by income, education, age, gender. Interviewees also encounter several financial inclusion barriers. Some economic policy recommendations are outlined to achieve better access for people to banking and microfinance.